Digital Innovation and Market Transformation for Sustainable Cultural Heritage Tourism Development (Beacon: International Journal of Education and Social Studies, 2025)
Cultural heritage tourism plays a strategic role in promoting economic growth while preserving the cultural and historical identity of communities. However, rapid technological advancement and changing tourist behavior require heritage destinations to adopt more innovative and sustainable approaches. This study aims to analyze the role of digital innovation and market transformation in supporting sustainable cultural heritage tourism development. A mixed-methods approach was employed, integrating quantitative and qualitative data collected through surveys, interviews, focus group discussions, and document analysis. The findings reveal that the implementation of digital technologies such as Virtual Reality (VR), Augmented Reality (AR), digital platforms, and technology-driven marketing strategies significantly enhances tourist satisfaction, visitor engagement, destination image, and awareness of cultural heritage preservation. Furthermore, market transformation through stakeholder collaboration, digital marketing, and community empowerment contributes positively to economic growth, community participation, and destination sustainability. The study concludes that the synergy between digital innovation and market transformation provides an effective pathway toward building competitive, inclusive, and sustainable cultural heritage tourism ecosystems.